2016
DOI: 10.1016/j.amepre.2016.02.012
|View full text |Cite
|
Sign up to set email alerts
|

Chronic Opioid Therapy and Central Sensitization in Sickle Cell Disease

Abstract: Chronic opioid therapy (COT) for chronic non-cancer pain is frequently debated, and its effectiveness is unproven in sickle cell disease (SCD). The authors conducted a descriptive study among 83 adult SCD patients and compared severity of disease and pain symptoms among those who were prescribed COT (n=29) with those who were not using COT. All patients completed baseline laboratory pain assessment and questionnaires between January 2010 and June 2014. Thereafter, participants recorded daily pain, crises, func… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
56
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 73 publications
(60 citation statements)
references
References 75 publications
3
56
1
Order By: Relevance
“…To determine if HbF played any role in pain sensitivity, we assessed this association limited only to the sickle cell cohort which showed fetal hemoglobin was negatively associated with pain (β= =−0.338, p=0.006 for 512 mN; β=−0.368, p=0.005 for 256 mN). Because another report suggested that nociceptive processing in SCD is affected by opioid therapy [40], regressions restricted to sickle cell subjects not treated with opioids (n=17) showed comparable results for association with HbF (256 Δ pain score β=−0.322, standard error=0.171 with p=0.08 and 512 Δ pain score for β=−0.365, standard error=0.178 with p=0.06), and suggest this association is independent of opioids.…”
Section: Resultsmentioning
confidence: 85%
See 1 more Smart Citation
“…To determine if HbF played any role in pain sensitivity, we assessed this association limited only to the sickle cell cohort which showed fetal hemoglobin was negatively associated with pain (β= =−0.338, p=0.006 for 512 mN; β=−0.368, p=0.005 for 256 mN). Because another report suggested that nociceptive processing in SCD is affected by opioid therapy [40], regressions restricted to sickle cell subjects not treated with opioids (n=17) showed comparable results for association with HbF (256 Δ pain score β=−0.322, standard error=0.171 with p=0.08 and 512 Δ pain score for β=−0.365, standard error=0.178 with p=0.06), and suggest this association is independent of opioids.…”
Section: Resultsmentioning
confidence: 85%
“…Although neither the regression with all subjects, nor regression excluding those taking opioids led to different conclusions, it is not possible to preclude opioid induced responses, especially in patients experiencing high pain burden that necessitates daily therapy. Indeed, a study of 38 SCD patients with high or low central sensitization showed high group responses were associated with opioid therapy [40]. Therefore, larger studies designed to determine the effect of opioids in sickle cell are needed [53].…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, while none of our patients on short‐acting opioids experienced continued pain, use of long‐acting opioids was associated with continued pain. This may be a reflection of more severe disease in this group; however, contributions from other factors, such as opioid‐induced hyperalgesia, central sensitization or genetic predisposition cannot be ruled out (Campbell et al , ; Carroll et al , ).…”
Section: Pre‐ and One‐year Post‐hsct Patient Characteristics Includinmentioning
confidence: 99%
“…Adults with SCD experience complications rarely seen in childhood, including leg ulcers, end‐stage kidney disease, restrictive lung disease, pulmonary hypertension, and retinopathy . Episodic acute pain may evolve into chronic pain due to peripheral nerve injury, central sensitization, and psychosocial factors . Men with SCD experience priapism, testicular infarction, and gonadal dysfunction; women have high peripartum morbidity and mortality risks .…”
Section: Natural History Of Scdmentioning
confidence: 99%